Lattices and ordered sets - Roman, Steven (Springer, 2008)
"...A thorough introduction to the subject of ordered sets and lattices, with an emphasis on the latter. Topic coverage includes: modular, semimodular and distributive lattices, boolean algebras, representation of distributive lattices, algebraic lattices, congruence relations on lattices, free lattices, fixed-point theorems, duality theory and more..."